2019
DOI: 10.1016/j.jadohealth.2018.12.006
|View full text |Cite
|
Sign up to set email alerts
|

A Descriptive Analysis of School and School Shooter Characteristics and the Severity of School Shootings in the United States, 1999–2018

Abstract: A B S T R A C TPurpose: The aim of the study was to determine whether characteristics related to the school, shooter, and guns used are associated with school shooting severity (casualty rates, fatality rates, and likelihood of fatality). Methods: We analyzed associations between individual-, school-, gun-level factors and school shooting severity in the United States from April 1999 through May 2018. Results: Handguns were used in most school shootings (81%); however, substantially, more fatalities occurred w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 7 publications
5
41
0
Order By: Relevance
“…We focused on high school students given the previous research indicating higher prevalence of handgun carrying among high school boys (Vaughn et al, 2016 ). Further, research has shown that school shooters over the last 19 years were of high school age and the majority of school shootings in that time occurred at high schools (Livingston, Rossheim, & Hall, 2019 ). The 2015 MIYHS sampled all 132 high schools in Maine, with 112 high schools participating.…”
Section: Methodsmentioning
confidence: 99%
“…We focused on high school students given the previous research indicating higher prevalence of handgun carrying among high school boys (Vaughn et al, 2016 ). Further, research has shown that school shooters over the last 19 years were of high school age and the majority of school shootings in that time occurred at high schools (Livingston, Rossheim, & Hall, 2019 ). The 2015 MIYHS sampled all 132 high schools in Maine, with 112 high schools participating.…”
Section: Methodsmentioning
confidence: 99%
“…The variation among school shootings is reflected in other studies in which cases were selected in different ways. In a study of 179 shootings at schools between 1999 and 2018, in which the sample was restricted to those occurring during or immediately before or after the school day when students were at risk, researchers found that only 54 of the shootings resulted in a fatality, with a range from 0 to 26 and mean of .7 (Livingston, Rossheim, & Hall, ). The shooters fell into three age groups: younger than 15 (31 cases, 17%), 15 to 19 (85, 47%), and 20 or older (29, 16%; age missing for 34 shootings).…”
Section: Heterogeneity Of Shootings In Schoolsmentioning
confidence: 99%
“…For example, in the United States, school shootings appear to have become more prevalent and more deadly in recent years (Lankford and Silver, 2020). School resource officers are often based in a local police department but responsible for school safety; they are charged with preparing plans to prepare for a mass attack (Livingston, Rossheim, & Hall, 2019). A deliberative approach could help the resource officer build connections with colleagues who could help stop the attack and take steps to mitigate damage.…”
Section: Reducing Cognitive Biases: Tools For Emergency and Crisis Mamentioning
confidence: 99%